Proceedings of the 2nd World Congress on Integrated Computational Materials Engineering (ICME) - Li, Mei.; Campbell, Carelyn; Thornton, Katsuyo; Holm, Elizabeth; Gumbsch, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book represents a collection of papers presented at the 2nd World Congress on Integrated Computational Materials Engineering (ICME), a specialty conference organized by The Minerals, Metals & Materials Society (TMS).
Keywords: Materials -- Analysis; Mechanical engineering; Engineering mathematics; Engineering -- Data processing; Characterization and Analytical Technique; Mechanical Engineering; Mathematical and Computational Engineering Applications